Evaluating psychosocial variables and social identity of Brazilian Paralympic athletes - Teixeira, Antonia Pinheiro (2018)
This exploratory research aimed to (1) assess the psychosocial variables of Brazilian Paralympic athletes, (2) verify how these variables relate to the athlete’s social identity, and (3) understand how Paralympic athletes perceive their identity. The study consisted of 153 Brazilian Paralympic athletes (122 males and 31 females with a mean age of 31.91 years, SD = 9.46), who answered a socio-demographic questionnaire; the instruments of the variables under study: (1) self-esteem, (2) self-efficacy, (3) locus of control, (4) affective well-being, and (5) social identity; and the open question «For me, being a Paralympic athlete means...» The results indicated that Paralympic athletes have high levels of social identity, self-esteem, self-efficacy, internal locus of control, and positive affective well-being, as well as low levels of external locus of control and negative affective well-being. Also, a positive correlation between social identity and self-esteem was found. The results revealed that Paralympic athletes’ identity is directly linked to their history of self-realization and the benefits of playing sports; however, they must still face some obstacles. This study highlights the importance of Paralympic athletes’ social identity, which benefits them not only as individuals, but through the deconstruction of stereotypes attributed to them by society.